A model of system-wide stress simulation: Market-based finance and the Covid-19 event - Giovanni Di Iasio; Spyridon Alogoskoufis; Simon Kördel; Dominika Kryczka; Giulio Nicoletti; Nicholas Vause (European Central Bank (ECB), 2022)
We build a model to simulate how the euro area market-based financial system may function under stress. The core of the model is a set of representative agents re ecting key economic sectors, which interact in asset, funding, and derivatives markets and face solvency and liquidity constraints on their behaviour. We illustrate the model's behaviour in a twolayer approach. In Layer 1 the deterioration in the outlook for the corporate sector triggers portfolio reallocation by the model's agents. Layer 2 adds a rating downgrade shock where a fraction of investment grade corporate bonds is downgraded to high yield, which creates further rebalancing pressure and price movements. The model predicts (i) asset ows (buying and selling of marketable securities) across agents and (ii) balance sheet losses. It also provides quantitative evidence on equilibrium effects of the macroprudential regulation of nonbanks, which we illustrate by varying investment fund cash buffers.We identify the effect of climate change-related regulatory risks on credit real- location, Our evidence suggests that effects depend borrower's region, Following an increase in salience of regulatory risks, banks reallocate credit to US firms that could be negatively impacted by regulatory interventions, Conversely, in Europe, banks lend more to firms that could benefit from environmental regulation, The effect is moderated by banks' own loan portfolio composition, Banks with a portfolio tilted towards firms that could be negatively affected by environmental policies increasingly support these firms, Overall, our results indicate that financial impli- cations of regulation associated with climate change appear to be the main drivers of banks' behavior.
Keywords: G17; G21; G22; G23; 330; Systemic risk; market-based nance; stress testing; COVID-19